THE INFLUENCE OF GOVERNMENT REGULATION NUMBER 23 OF 2018, TAX KNOWLEDGE AND USE OF ANNUAL E-SPT ON INDIVIDUAL MICRO SMALL AND MEDIUM ENTERPRISES (MSME) TAXPAYER COMPLIANCE IN 2018-2020 AT KPP PRATAMA TIGARAKSA - Niasari, Elva; Andi; Mukhtar (Management Science Research Journal, 2023)
This study aims to determine the effect of government regulation number 23 of 2018, tax knowledge and annual E-SPT utilization on MSME taxpayer compliance at the Tigaraksa Primary Tax Service Office. The population in this study all individual MSME taxpayers at the Tigaraksa Pratama Tax Service Office, and the sample used was 100 taxpayers. Thisresearch is quantitative. The type of data in this study is primary with data sources using questionnaires, data analysis methods used is multiple linear regression. The results of this study indicate that government regulation number 23 of 2018 and taxknowledge have no effect on MSME taxpayer compliance, while the use of the annual E-SPT has an effect on MSME taxpayercompliance